Application value of multiparametric MRI for evaluating iron deposition in the substantia nigra in Parkinson's disease - Cao, Qing; Huang, Jinjin; Tang, Dongping; Qian, Hao; Yan, Kun; Shi, Xun; Li, Yaowei; Zhang, Jiangong (Frontiers in Neurology, 2023)
Objective This study aimed to investigate the application value of multi-parametric magnetic resonance imaging (MRI) in the diagnosis of iron deposition in the substantia nigra dense zone in Parkinson's disease (PD) and to evaluate the diagnostic value of the correlation among multi-parametric imaging indicators, clinical stage, and disease duration. Materials and methods Thirty-six patients with clinically confirmed PD and 36 healthy controls were enrolled. The disease course was recorded, and PD severity was graded using the Hoehn–Yahr (H–Y) scale. All subjects underwent magnetic sensitivity weighted imaging (SWI), neuromelanin magnetic resonance imaging (NM-MRI), and a T2*mapping sequence. Based on the fusion of the NM-MRI and SWI amplitude maps, phase maps, and T2*MAPPING value maps, NM-MRI was used to delineate the dense zone of the substantia nigra, which was divided into three sub-regions: upper, middle, and lower. In this way, the amplitude, phase, and R2* values of each sub-region and the average value of the sum of the three sub-regions were obtained simultaneously in the SWI amplitude, phase, and T2*MAPPING maps. The multi-parameter imaging indices were compared between the two groups, and the correlation between them and clinical indices was evaluated in the PD group. Results The upper (amplitude, phase value, R2* value), middle, and lower (amplitude) right substantia nigra compact zones were significantly different between the PD and control groups. The upper (phase value, R2* value) and middle (amplitude) areas of the left substantia nigra compact zone were also significantly different between the two groups (all P < 0.05). The mean values (amplitude, phase value, R2* value) of the right substantia nigra densification zone and the mean values (phase value) of the left substantia nigra densification zone were also significantly different (all P < 0.05). Amplitudes in the middle and lower parts of the right substantia nigra dense zone were negatively correlated with the H–Y grade (middle: r = −0.475, P = 0.003; lower: r = −0.331, P = 0.049). Amplitudes of the middle and lower parts of the dense zone of the left substantia nigra were negatively correlated with the H–Y grade (middle: r = −0.342, P = 0.041; lower: r = −0.399, P = 0.016). The average amplitude of the right substantia nigra compact zone was negatively correlated with the H–Y grade (r = −0.367, P = 0.027). The average R2* value of the compact zone of the left substantia nigra was positively correlated with the H–Y grade (r = 0.345, P = 0.040). Conclusion Multiparametric MRI sequence examination has application value in the evaluation of iron deposition in the dense zone of the substantia nigra in PD. Combined with NM-MRI, fusion analysis is beneficial for accurately locating the substantia nigra compact zone and quantitatively analyzing the iron deposition in different sub-regions. Quantitative iron deposition in the middle and lower parts of the substantia nigra dense zone may become an imaging biological indicator for early diagnosis, severity evaluation, and follow-up evaluation of PD and is thus conducive for clinical diagnosis and treatment evaluation.